2012
DOI: 10.1080/00222895.2012.654525
|View full text |Cite
|
Sign up to set email alerts
|

A Two Process Memory-Based Account for Mental and Physical Practice Differences

Abstract: The authors investigated the underlying processing structures for mental and physical practice. Participants mentally or physically performed 4 tasks during practice. Halfway through practice, 2 tasks were switched from mental to physical practice, or vice versa. After completing practice trials, participants performed 2 retention tests. The first retention test required memory retrieval and the second retention test reinstated the practice context and did not require memory retrieval. Measures of response ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 29 publications
0
13
0
1
Order By: Relevance
“…This interpretation is in accordance with previous fi ndings of no diff erences between two such conditions ( Zecker, 1982 ;Ryan, 1983 ;Gomes, et al ., 2012 ). On the other hand, other studies have shown best per-410 formance when mental practice was performed before physical practice ( Etnier & Landers, 1996 ;Millard, et al ., 2001;Raisbeck, et al ., 2012 ).…”
Section: Hypothesismentioning
confidence: 99%
See 2 more Smart Citations
“…This interpretation is in accordance with previous fi ndings of no diff erences between two such conditions ( Zecker, 1982 ;Ryan, 1983 ;Gomes, et al ., 2012 ). On the other hand, other studies have shown best per-410 formance when mental practice was performed before physical practice ( Etnier & Landers, 1996 ;Millard, et al ., 2001;Raisbeck, et al ., 2012 ).…”
Section: Hypothesismentioning
confidence: 99%
“…To investigate the eff ects of mental practice, a combined practice group (mental and physical practice together) is traditionally used ( Feltz & Landers, 1983 ;Overdorf, et al ., 2004 ;Raisbeck, Wyatt, & Shea, 2012 ). This is another concerning aspect of implementation in the mental practice literature.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To accomplish optimal learning environments, limitations with respect to motor learning literature should also be considered. Specifically, many classic studies tuse terms such as "practice" or "acquisition" interchangeable with "training", as they have relied on short-term interventions of one or two days and "retention/learning" assessments following rest periods as low as 20 min [139,140] and typically not more than 24 h [78,159,160]. While still important contributions to the literature, the nuanced differences between motor performance and motor learning [79,147] are not always clearly delineated, specifically as to whether a learned behavior may actually be retained for an extended time period.…”
Section: Acl Injury and Neuroplasticity In Youth: An Overlapping Timementioning
confidence: 99%
“…De modo geral, quando comparadas situações de nenhum tipo de prática, PM, PF e PF+PM os estudos têm apresentado que a aprendizagem ocorre menos com nenhuma prática seguido de somente PM, somente PF e PF+PM. Sendo importante destacar que nenhuma prática e somente PM são consideravelmente inferiores a somente PF e PF+PM [3][4][5][6][7][8][9][10][11][12][13][14] . A efetividade da PM tem sido explicada de duas formas.…”
unclassified